Design And Construction Of Parking Lot Security System Using Internet Of Things And RFID Technology In Megaland Housing Complex - Riza Salma; Al-Khowarizmi (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
The parking lot security system is a very important aspect in maintaining the security and comfort of residents in a housing complex. This thesis aims to design and build a parking lot security system using Internet of Things (IoT) and Radio Frequency Identification (RFID) technology at the MegaLand housing complex. This system integrates IoT devices to monitor and control vehicle entry and exit access, and uses RFID technology to identify each vehicle that has a parking access permit. The use of this technology is expected to increase the efficiency and effectiveness of parking lot management, reduce the risk of theft, and make it easier for residents to access the parking area. The results of implementing this system show a significant improvement in the security and parking management aspects of the MegaLand Housing Complex.